2021
DOI: 10.3390/pathogens10050615
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Contamination in Hospital Environment Has the Potential to Colonize Preterm Newborns’ Nasal Cavities

Abstract: Infants born before 28 weeks are at risk of contracting healthcare-associated infections (HAIs), which could be caused by pathogens residing on contaminated hospital surfaces. In this longitudinal study, we characterized by NGS the bacterial composition of nasal swabs of preterm newborns, at the time of birth and after admission to the Neonatal Intensive Care Unit (NICU), comparing it with that of the environmental wards at the time of delivery and during the hospitalization. We characterized the resistome on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 91 publications
0
26
0
Order By: Relevance
“…21 HAI incidence is particularly high in pediatric wards, due to the high susceptibility of children to infections. 22 Premature babies are particularly exposed to the risk of contracting uncommon and rare HAIs, 23 and we recently reported colonization of preterm newborns by environmental Intensive Care Unit (ICU)-resistant microbes, 24 supporting the significant potential contribution of environmental hospital microbes in children with HAIs.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…21 HAI incidence is particularly high in pediatric wards, due to the high susceptibility of children to infections. 22 Premature babies are particularly exposed to the risk of contracting uncommon and rare HAIs, 23 and we recently reported colonization of preterm newborns by environmental Intensive Care Unit (ICU)-resistant microbes, 24 supporting the significant potential contribution of environmental hospital microbes in children with HAIs.…”
Section: Introductionmentioning
confidence: 89%
“…Briefly, duplicate samples were collected from surfaces and incubated anaerobically ( Clostridium medium) or aerobically (all the remaining media) for 24–48 h (bacteria), or at 25 °C for 72 h (mycetes). 24 , 32 At the end of incubation, colony-forming units (CFU) were counted, and S. aureus identification was performed on Baird–Parker medium and confirmed by API Staph (bioMerieux, Inc, Durham, NC, USA), as previously described. 7 …”
Section: Methodsmentioning
confidence: 99%
“…For instance, Staphylococcus spp., and Streptococcus spp. have been detected in the noses of babies after NICU hospitalization using 16S rRNA gene amplicon sequencing (Cason et al, 2021). Including the study by Cason et al, findings from recent studies suggest that environmental hospital surface contamination (i.e.…”
Section: Alpha and Beta Diversity Differences Between Several Baseline And Post-intervention Surfacesmentioning
confidence: 99%
“…Staphylococcus spp.) can greatly contribute to the transmission of nosocomial pathogens and the occurrence of HAIs (Suleyman et al, 2018;Cason et al, 2021). While this study reports on the microbial community composition of active microbes from ICU surfaces Pre and Post cleanSURFACES ® intervention, more work is required to assess the potential impact of cleanSURFACES ® on the transmission of nosocomial pathogens and HAI occurrence.…”
Section: Alpha and Beta Diversity Differences Between Several Baseline And Post-intervention Surfacesmentioning
confidence: 99%
“…Vertical molecular studies have provided more insights into CoNS infections and the routes of their acquisitions. The next generation sequencing (NGS) and quantitative-PCR (qPCR) microarray analyses confirmed the impact of the hospital environment microbiome on S. aureus and S. epidermidis nasal colonization rates [22]. Moreover, studies on isolates from 96 institutions in 24 countries identified the global emergence of multidrug-resistant, hospital-adapted lineages of S. epidermidis (two ST2 and one ST23).…”
Section: Introductionmentioning
confidence: 80%